Etnobotânica e práticas agroecológicas na comunidade rural Rio dos Couros, Cuiabá, MT, Brasil - Costa, Ineilian Bruna Correa da [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The objective of this study was to perform the socioeconomic and cultural survey of the community and of your ethnic knowledge about the plant diversity in the landscape units, as well as identify the agroecological methods applied in productive dimension of rural community Rio dos Couros, Cuiabá, MT. The methodology adopted was the so-called snowball. Data collection occurred through semi-structured interviews, direct observation, field diary and agroecological form, applied during free walking (Walk- In-The-Woods). Fifty individuals were interviewed between 25-74 years (50% male and 50% female) with the majority of origin in the community with a good part of migrants residing in more than 50 years site. Most also have incomplete elementary school. The rent of the interviewed varies from 300 to 2712 real coin and the main relion cited was the Catholic. Data as age difference, residence time and income were elements that interfered in the level of ethnobotanical and agroecological knowledge. In ethnobotanical survey in the yard were registered 144 species distributed in 52 families, categorized with feed (42%), medical (40%), ornamental (10%), other (6%) and religious (2%). The most representative were the families Fabaceae (14 species) and Asteraceae (10 species). The arboreal and herbaceous growth habit were the most characteristic. In the woods were recorded 82 species distributed in 38 families, categorized as feed (13%), medical (58%), ornamental (4%), other (23%) and religious (2%). The most representative family was Fabaceae (15 species) and most species presents arboreal habit, followed by the shrubby. Medicinal species in general the leaf (51%) is the most used part and the main method of preparation is tea (decoction) with 33% of the votes. On the farm, the most cited species were cassava, corn and pumpkin / squash being the Curcubitaceae the most cited family. Regarding the adopted ...

Objetivou-se neste estudo realizar o levantamento socioeconômico e cultural da comunidade e de seu etnoconhecimento acerca da diversidade vegetal nas unidades de paisagem, bem como identificar os métodos agroecológicos aplicados na dimensão produtiva da comunidade rural Rios dos Couros, Cuiabá, MT. A metodologia adotada foi a denominada bola de neve. A coleta de dados ocorreu mediante entrevista semi-estruturada, observação direta, diário de campo e formulário agroecológico, aplicados durante caminhadas livres (Walk-in-The-Woods). Foram entrevistados 50 indivíduos entre 25 a 74 anos (50% do sexo masculino e 50% do feminino) sendo a maioria de origem da comunidade com boa parte dos migrantes residindo no local a mais de 50 anos. A maioria também possui o ensino fundamental incompleto. A renda por entrevistado varia de 300 a 2.712 reais e a principal religião citada foi a católica. Dados como diferença de idade, tempo de moradia e renda foram elementos que interferiram no nível de conhecimento etnobotânico e agroecológico. No levantamento etnobotânico no quintal foram registradas 144 espécies distribuídas em 52 famílias, categorizadas com uso alimentar (42%), medicinal (40%), ornamental (10%), outros (6%) e religioso (2%). As famílias mais representativas foram a Fabaceae (14 espécies) e Asteraceae (10 espécies). O hábito de crescimento arbóreo e herbáceo foram os mais característicos. Na mata foram registradas 82 espécies distribuídas em 38 famílias, categorizadas como alimentar (13%), medicinal (58%), ornamental (4%), outros (23%) e religioso (2%). A família mais representativa foi a Fabaceae (15 espécies) e a maioria das espécies apresenta hábito arbóreo, seguido do arbustivo. Nas espécies medicinais em geral a folha (51%) é a parte mais utilizada e o principal modo de preparo é o chá (decocção) com 33% das indicações. Na roça ...
Ethnobotany and agroecological practices in the rio dos Couros rural community, MT, Cuiabá, Brazil
Keywords: Agricultura familiar - Brasil; Etnobotânica; Biodiversidade; Ecologia agrícola; Family farms